Dukungan Irlandia Terhadap Upaya Perdamaian di Palestina - Rostamaji Kurniawan (Indonesia Center for Middle East Studies, 2017)
This article aimed at reviewing Ireland’s support for reconciliation of Palestine. Conflict of Palestine and Israel, in essence, has characteristics that are almost equal to conflict took place in Ireland. Therefore, the reconciliation process of Irish conflict underlay Ireland’s support towards Palestinian. This article is written using literature review. The finding of this article is that Ireland using soft diplomacy in helping Palestinians, namely political support through the UN as well as statements of support from Irish politicians, economic pressure (through boycott), financial aid, and accommodating Palestinian refugees. But at the same time, Ireland continues to do economic cooperation with Israel.